Evaluation of three rapid low-resource molecular tests for Nipah virus - Pollak, Nina M.; Olsson, Malin; Marsh, Glenn A.; Macdonald, Joanne; McMillan, David (Frontiers in Microbiology, 2023)
Accurate and timely diagnosis of Nipah virus (NiV) requires rapid, inexpensive, and robust diagnostic tests to control spread of disease. Current state of the art technologies are slow and require laboratory infrastructure that may not be available in all endemic settings. Here we report the development and comparison of three rapid NiV molecular diagnostic tests based on reverse transcription recombinase-based isothermal amplification coupled with lateral flow detection. These tests include a simple and fast one-step sample processing step that inactivates the BSL-4 pathogen, enabling safe testing without the need for multi-step RNA purification. The rapid NiV tests targeted the Nucleocapsid protein (N) gene with analytical sensitivity down to 1000 copies/µL for synthetic NiV RNA and did not cross-react with RNA of other flaviviruses or Chikungunya virus, which can clinically present with similar febrile symptoms. Two tests detected 50,000-100,000 TCID50/mL (100-200 RNA copies/reaction) of the two distinct strains of NiV, Bangladesh (NiVB) and Malaysia (NiVM), and took 30 min from sample to result, suggesting these tests are well suited for rapid diagnosis under resource-limited conditions due to rapidity, simplicity, and low equipment requirements. These Nipah tests represent a first step toward development of near-patient NiV diagnostics that are appropriately sensitive for first-line screening, sufficiently robust for a range of peripheral settings, with potential to be safely performed outside of biohazard containment facilities.